Characteristic Comparison of CHD for Active Smoker by Smoking Characteristic - Desy Diastutik (Universitas Airlangga, 2017)
Coronary Heart Disease (CHD) is a type of cardiovascular disease that has highest level of morbidity and mortality among non communicable disease group. One of the factor that contribute for coronary heart disease is smoking characteristic. The research was aimed to analyze characteristic comparison of coronary heart disease for active smoker by smoking characteristic. The research was observational study using cross sectional design. Thirty eight active smokers were involved as research sample who are patients at RSUD Sidoarjo, according to some criteria.The variables of smoking characteristic were duration of smoking, type of cigarette, amount of cigarette per day, and time of smoking. The research was done on May 2016 using accidental sampling as the technique. Data analyze was using Epi info software to show the characteristic comparison and continued analyze by descriptive. The results of the research were highest partly among patient with coronary heart disease and patient with non coronary diasease were had been smoking for ≥33 years, spent less than 13 cigarette per day, and didn't smoke soon after wake up in the morning. The conclusion of the research are the highest characteristic coronary heart disease for active smoker by smoking characteristic was type of cigarette, and the lowest characteristic coronary heart disease for active smoker by smoking characteristic was duration of smoking. Keywords: number of cigarette, coronary heart disease, duration of smoking, type of cigarette, time of smoking